Phatic Utterances By English Teachers At Muhammadiyah Vocational High School in Klaten - Chasanah, Ulfah (2016)
ABSTRACT ULFAH CHASANAH, S200120053. PHATIC UTTERANCES BY ENGLISH TEACHERS AT MUHAMMADIYAH VOCATIONAL HIGH SCHOOL IN KLATEN. THESIS. MUHAMMADIYAH UNIVERSITY OF SURAKARTA 2015 Phatic Utterances (then called as phatic communion) firstly is stated by Malinowski (1923: 476) in The Problem of Meaning in Primitive Language which is described as "language used in free, aimless, social intercourse". While Coupland, Coupland and Robinson (1992: 208) said about phatic communion as a type of speech in which ties of union and created by a mere exchange of words when people aimlessly gossip. Politeness Strategy, according to Brown and Levinson is a strategy that is used to prevent a violation of the hearer's face or to save the hearer's face. The study aims to describe: 1) Types of phatic Utterances used by English Teachers at Muhammadiyah Vocational High School in Klaten? and 2) Politeness Strategies are included in phatic utterances used by English Teachers at Muhammadiyah Vocational High School in Klaten? The type of this study is descriptive qualitative. The data were obtained from 7 DCTs which are set to be replied by English Teachers at Muhammadiyah Vocational High School in Klaten. There are 25 English teachers who are concern to give their opinions to the situation sets in DCTs given. The findings of this thesis are concerned to the data found in DCT which analyzed in two categorizes: First, The Types of Phatic Utterances which are accommodated from the data found in seven DCT stated: (a) Doing Collegiality (b) To be the icebreaker that clears the way for more intimate conversation (c)To send or to receive informative communication (d) To maintain the contact with the person we are talking to (e) To create or to maintain "bonds of sentiment" between speakers (f) To express the addressor's intention to install, to continue or to finish the contact (g) Phatic is more interesting and more diverse in special setting. The data found in the type of phatic utterances are formed in certain expressions which explain the situation set in each DCT. Second, Politeness Strategies in Phatic Utterances, where the data found in each DCT are suited to the strategies include in Politeness Strategy; Bald On-Record Strategy, Positive Politeness Strategy, negative Politeness Strategy, and Off-Record Strategy. Key words: Phatic Utterances, Politeness Strategy.